Line maintenance within transmission expansion planning: a multistage framework - Mahdavi, Meisam [UNESP]; Sabillon, Carlos [UNESP]; Bagheri, Amir; Romero, Ruben [UNESP] (Inst Engineering Technology-iet, 2019)
Maintenance in transmission networks is an economical way to reduce upgrading network costs without decreasing its reliability. Hence, new studies regarding transmission expansion planning (TEP) must take into account the effects of maintenance in order to obtain realistic and economic expansion investment plans. This work presents a novel framework for multistage TEP, considering line maintenance, i.e. the expansion cost of the transmission system, network losses, costs of old-line replacement and maintenance, cost of newly constructed line maintenance, and cost of replaced line maintenance, are simultaneously optimised. The advantage of this approach is the fact that the lifetimes of the lines that are replaced, retained, and added to the transmission system are changing during the expansion horizon. These lifetimes have an impact on the maintenance expenses. Annual maintenance costs are also affected by the inflation rate. Hence, both the lifetime and inflation rate roles are integrated into the proposed model. The robustness and effectiveness of the model are tested on the IEEE 24-bus test system, using a particle swarm optimisation algorithm. The results show that the proposed formulation finds more economic investment plans for TEP when compared with those found using static formulations considering the maintenance available in specialised literature.
Keywords: power transmission planning; power distribution planning; maintenance engineering; investment; particle swarm optimisation; costing; optimisation; power transmission economics; transmission expansion planning; multistage framework; transmission networks; upgrading network costs; realistic expansion investment plans; economic expansion investment plans; multistage TEP; expansion cost; transmission system; network losses; old-line replacement; newly constructed line maintenance; replaced line maintenance; lifetimes; expansion horizon; maintenance expenses; annual maintenance costs; IEEE 24-bus test system; economic investment plans